Commissural nucleus of the solitary tract is important for cardiovascular responses to caudal pressor area activation - Takakura, Ana Carolina; Moreira, Thiago Santos; Menani, José Vanderlei [UNESP]; Campos, Ruy Ribeiro; Colombaria, Eduardo (Elsevier B.V., 2007)
The nucleus of the solitary tract (NTS) is the site of the first synapse of cardiovascular afferent fibers in the central nervous system. Important mechanisms for cardiovascular regulation are also present in the caudal pressor area (CPA) localized at the caudal end of the ventrolateral medulla. In the present study we sought to investigate the role of the commissural subnucleus of the NTS (commNTS) on pressor and tachycardic responses induced by L-glutamate injected into the CPA. Male Holtzman rats (n=8 rats/group) anesthetized with urethane (1.2 g/kg of body weight, iv) received injections of the GABAA receptor agonist muscimol into the commNTS. Unilateral injection of L-glutamate (10 nmol/ 100 nL) into the CPA increased mean arterial pressure (MAP, 31 4 mm Hg, vs. saline: 3 +/- 2 mm Hg) and heart rate (HR, 44 8 bpm, vs. saline: 10 7 bpm). inhibition of commNTS neurons with muscimol (120 pmol/60 nL) abolished the increase in MAP (9 4 mm Hg) and HR (17 7 bpm) produced by L-glutamate into the CPA. The present results suggest that the pressor and tachycardic responses to CPA activation are dependent on commNTS mechanisms.
Keywords: ventrolateral medulla; sympathetic; hypertension; excitatory amino acid; Muscimol; NTS; CPA